Vicisitudes en el tratamiento del daño moral por la jurisprudencia laboral peruana - Briones Quispe, Milko (2019)
The ideal of Legal certainty seems to elude us because of divergent and heterogeneous case law. In Peruvian labour case law, ruling of non-pecuniary damage cases often deviates from precedent criteria; thus, there is no safe criterion in matters such as –for example– its specific elements, or when does someone is obliged to prove it or when presumptions are available.This article aims to highlight the lack of stability among the non-pecuniary damage labour case law ruling criteria. The author begins by introducing the concept and premises of non-pecuniary damage from tort law theory. Furthermore, the author reflects on Peruvian labour case law ruling criteria referred to compensation for non-pecuniary damage in the context of arbitrary, uncaused or fraudulent dismissal. At last, the author delves on the need of adhering to precedent criteria for the ruling of non-pecuniary damage cases.